2022
DOI: 10.1007/s42976-022-00302-0
|View full text |Cite
|
Sign up to set email alerts
|

Sitotroga cerealella-resistant mexican maize races (Zea mays L.), new sources of resistance for commercial maize breeding

Abstract: Sitotroga cerealella (Oliv.) (Lepidoptera: Gelechiidae) is one of the most important post-harvest pests of maize Zea mays L. Some Mexican maize races (Z. mays) could be a novel source of resistance against S. cerealella to improve commercial maize varieties, lines and hybrids. We studied the resistance of Mexican maize races, recollected at Chihuahua State to S. cerealella. We focused on antibiosis and tolerance of maize to S. cerealella. Cristalino-079 maize race shows low level of consumption in grams and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Arnason et al [10], Abebe et al [11], and Serratos et al [12] have identified some maize accessions with a high level of tolerance to S. zeamais. We have detected varieties with resistance to two storage pests, Sitotroga cerealella and S. zeamais, and Cristalino-079, in a previous study, had only 4.5% weight loss caused by S. cerealella [44]. Meanwhile, in the current study, we observed 4.2% weight loss in a nine-month period of obligate feeding and 8.5% weight loss in an eight-month period under free-choice conditions.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Arnason et al [10], Abebe et al [11], and Serratos et al [12] have identified some maize accessions with a high level of tolerance to S. zeamais. We have detected varieties with resistance to two storage pests, Sitotroga cerealella and S. zeamais, and Cristalino-079, in a previous study, had only 4.5% weight loss caused by S. cerealella [44]. Meanwhile, in the current study, we observed 4.2% weight loss in a nine-month period of obligate feeding and 8.5% weight loss in an eight-month period under free-choice conditions.…”
Section: Discussionsupporting
confidence: 46%
“…The differences in the percentage of weight loss could be due to pest diversity, exposure time, temperature, etc. Therefore, we trust that Cristalino-079 could be used in breeding programs for resistance to S. cerealaella and S. zeamais [44]. In addition, the Azul race can be used for maize genetic improvement since it presents a good level of resistance to S. zeamais.…”
Section: Discussionmentioning
confidence: 97%
“…Sitotroga cerealella infests maize, wheat, and rice, resulting in substantial direct damage through larval feeding and increased susceptibility to secondary insect pests and fungi. 4 Sitotroga cerealella infestation during storage contributes to losses of up to 13% in grain weight and 76% in the number of damaged grains, 5 which pose significant economic challenges and threaten food security.…”
Section: Introductionmentioning
confidence: 99%